Phylogenetics of Embioptera (=Embiidina) - Szumik, Claudia Adriana (2003)
A morphological analysis using 70% of the described genera and 45% of the known species of Embioptera is described and discussed. The results indicate that many of the non-male terminalia characters are informative.